Evaluation of the safety and quality of wash water during the batch washing of Pangasius fish (Pangasius hypophthalmus) in chlorinated and non-chlorinated water. (May 2016) - Tong Thi, Anh Ngoc; Sampers, Imca; Van Haute, Sam; Samapundo, Simbarashe; De Meulenaer, Bruno; Heyndrickx, Marc; Devlieghere, Frank
Abstract: This study investigated the continuous dosing of chlorine to the wash water by means of a pump to maintain antimicrobial levels of free chlorine in the wash water during the washing of 12 batches of Pangasius fillets. In comparison to the control (no chlorination), total psychrotrophic bacteria were reduced by between 2 and 4 log CFU/100 ml. After the final batch was washed, total chlorine and organic matter in the water sampled had accumulated to 482.9 ± 17.0 ppm and 4447.5 ± 187.4 mg O2 /L, respectively. However, only 8.9 ± 1.3 μg/L of trihalomethanes was formed in the chlorinated wash water whereas no trihalomethanes were detected in the washed Pangasius fillets after rinsing. It was concluded that the Pangasius fillets washed in chlorinated water continuously dosed with chlorine were safe for human consumption even after a throughput of 12 batches. However, the organoleptic properties of Pangasius fillets washed in the final batch differed significantly from those washed earlier batches. Highlights: A great potential of continuous dosing system for washing Pangasius was illustrated. Wash water can be reused for several batches Pangasius. Continuous dosing system avoids cross contamination of washed products. Concerns of sensory quality and chemical safety of washed Pangasius were discussed.